A novel anti-disturbance fast terminal sliding mode method based on DC-DC boost converter - LIANG Bo; XU Xiang; NIU Rongchao; ZHANG Hongyu; ZHANG Xuan; LI Yuren (Xibei Gongye Daxue Xuebao)
In order to stabilize the bus voltage and match the power demand, this paper proposes a new fast terminal sliding mode control strategy to enhance the system's anti-disturbance ability for the DC-DC boost converter. Firstly, a full order sliding mode surface is proposed to ensure finite time convergence of the system state, and an integral type switching control term is proposed to handle large disturbances. Then, perturbation observation is used to calculate system uncertainty which further enhances robustness and reduces chattering. Next, a parameter update mechanism is proposed to calculate the model parameters of the current working point, which helps to improve control performance and enhance flexibility in dealing with different working conditions. Finally, the effectiveness of this method is verified through simulation.